Structural and Functional Improvements of Coastal Ecosystem Based on Artificial Oyster Reef Construction in the Bohai Sea, China - Wang, Xu; Feng, Jie; Lin, Chenggang; Liu, Hui; Chen, Muyan; Zhang, Yunling (Frontiers in Marine Science, 2022)
Oyster reefs are gaining more and more attention in marine ranching and coastal ecosystem restoration, but tremendous knowledge gaps still exist. In this study, we developed trophic models for the established artificial oyster reef (EAOR), newly deployed artificial oyster reef (NAOR), and non-reef bare substratum (NBS) ecosystems located in the Bay of Xiangyun, Bohai Sea, China, to assess the benefits of artificial oyster reef construction and to characterize the unique role of these reefs in coastal management. The analysis showed that the EAOR and NAOR ecosystems were similar to each other, but both were greatly different than the NBS ecosystem. Reefs showed greater “ecological size” and stronger top-down effects compared to the bare area. The ecosystems were not yet mature, but the EAOR and NAOR ecosystems had more complicated trophic relationships, greater potential to withstand perturbations, and higher biological carrying capacities of commercial organisms compared to the NBS ecosystem. These results demonstrated that artificial oyster reef construction resulted in great advantages to the ecosystem. For example, oysters became the structuring functional group and played a critical role in the trophic structure of the reef areas. The phytoplankton/detritus-oysters-carnivorous macrobenthos pathway developed and became dominant in these areas, thereby contributing to highly efficient secondary production. The ratios of total primary production/total respiration were < 1, indicating that the reef ecosystems responded effectively to nutrient inputs from adjacent ecosystems. We speculate that water exchange might be a critical factor influencing the maintenance of the system. Long-term monitoring of the EAOR and NAOR should be implemented for oyster protection and to assess the need to manipulate carnivorous macrobenthos to keep the systems in balance. Results of this study could benefit the restoration, exploitation, and management of oyster reefs. Further studies should take the adjacent ecosystems and anthropogenic activities into account.